SYSTEMATIC REVIEW: EVALUATION OF CYTOKINE STORM TREATMENT FROM COVID 19 PATIENT BASE ON CLINICAL TRIAL - ARNANDA, NINDI; RAMATILLAH, DIANA LAILA (International Journal of Applied Pharmaceutics, 2022)
These cytokine storms are extremely dangerous. Cytokine storm is considered the reason for the high mortality rate of COVID 19 patients. An undetected reason causes a Cytokine storm in a patient, but this is associated with the characteristics of a person's immune system. Most COVID-19 patients recover with mild and moderate symptoms within one week; some develop severe pneumonia in the second week, followed by cytokine storm, ARDS, multiorgan failure, and disseminated intravascular coagulation (DIC) within the 3rd week. The high mortality rate in COVID-19 patients is most likely due to a cytokine storm in the patient's body. Cytokines are also immune system proteins that regulate interactions between cells and trigger immune reactivity, both in innate and adaptive immunity. To evaluate all treatments that can be used during the treatment of cytokine storm in COVID-19 patients based on clinical trials. Systematic Literature Review (SLR) about studies researching the treatment of cytokine strom in COVID-19 patients. Accumulated treatment was calculated using the confidence ratio for the random effects meta-analysis method of medium and high-quality data. Based on the literature on clinical trials, we can use Tocilizumab, Ruxolitinib. Baricitinib, Itolizumab, Zilucoplan, Stem Cells (MSC transplantation, Umbilical cord mesenchymal stromal cells, and Placenta‐derived decidua stromal cells), Anakinra, Beta-glucans (AFO-202 and N-163 of a black yeast Aureobasidium pullulans), LDRT (Low-dose radiation therapy), ALS (Artificial-liver blood-purification system), and CP (Convalescent plasma) medication for treating COVID-19 patient with cytokine storm syndrome. The use of each treatment has its advantages and disadvantages. However. All of the above therapies have shown effectiveness in treating cytokine storms in clinical trials.